Implementation and evaluation of change-over speed in plug-in hybrid electric two wheeler. (15th August 2016) - Amjad, Shaik; Rudramoorthy, R.; Sadagopan, P.; Neelakrishnan, S.
Abstract: In Asia, two wheelers are popular mode of transportation to a large group of people because of their relative affordability and ability to maneuver in heavy city traffic. However, the rate of fuel consumption and emission contribution by them, especially in urban areas need more attention to improve sustainability of energy and air quality. Recently, plug-in hybrid technology has been emerged as one of the most promising alternatives in reducing petroleum consumption and emission. This paper presents the implementation of plug-in hybrid technology on a two wheeler by formulation of novel control strategy suitable for Indian city driving needs. Experimental investigations on hub motor and IC (internal combustion) engine has been carried out to fix the change-over speed in hybrid mode, followed by road test on prototype vehicle. The performance of prototype vehicle on IDC (Indian driving cycle) simulated road pattern and actual road driving, confirmed the change-over speed of vehicle in hybrid mode. The converted plug-in hybrid electric two wheeler also demonstrated the drive strategy adopted for higher energy efficiency up to 2.5 times. So, plug-in hybrid electric two wheelers show significant improvements in fuel economy by replacing petroleum fuel with electricity for portions of trip to achieve nations' energy security. Highlights: Implementation of plug-in hybrid concept for two wheelers suitable for city driving. Investigation on hub motor, engine and prototype vehicle to fix change-over speed. Plug-in hybrid electric two wheeler demonstrates 2.48 times higher fuel efficiency. Significant improvements in fuel economy help to achieve nations' energy security.